Evaluation of Amikacin Regimens, Cmax/MIC Ratios, and Clinical Outcomes in a Hospital at Yogyakarta, Indonesia - Firdhani Satia Primasari; Nidya Afriana Fitria Dewi; Fita Rahmawati; Arief Rahman Hakim (Borneo Journal of Pharmacy, 2026)
Amikacin is widely used to treat infections caused by gram-negative bacteria. Its narrow therapeutic range necessitates plasma concentration monitoring through Therapeutic Drug Monitoring (TDM). However, limited infrastructure has restricted TDM implementation in many Indonesian healthcare settings. This study aims to evaluate amikacin dosing, estimate blood concentrations using pharmacokinetic equations, assess the PK/PD profile, and analyze clinical outcomes. This descriptive-analytic study employed a retrospective cross-sectional design. It was conducted at a hospital in Yogyakarta by collecting data on amikacin dosing regimens, patient clinical outcomes, serum creatinine levels, and antibiotic sensitivity test results. The study subjects were hospitalized patients with infections who received amikacin therapy. Descriptive analysis was performed on patient characteristics, while estimated blood drug levels and PK/PD profiles were calculated using pharmacokinetic formulas and analyzed descriptively. A total of 44 amikacin dosing regimens from 40 patients met the inclusion and exclusion criteria. Of these, 39 regimens were appropriate according to dosing guidelines, and 26 (66.7%) resulted in favorable clinical outcomes. In contrast, five inappropriate regimens were associated with poor clinical outcomes. Among the 39 appropriate regimens, only 18 (46.2%) achieved the target peak plasma concentration (Cmax). Furthermore, of these 18 regimens, only two (11.1%) achieved the target Cmax/MIC ratio, with one associated with a favorable clinical outcome and one without improvement. These findings suggest that, despite appropriate dosing, most amikacin regimens failed to achieve the optimal Cmax/MIC ratio required for effective clinical outcomes, highlighting the potential value of TDM and individualized dosing strategies to optimize amikacin therapy.